Analysis of Customer Satisfaction in Mediating Customer Value and Cafe Atmosphere towards Brand Image - Teguh Widodo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the increasingly competitive café industry, creating strong customer experiences is essential for building a favorable brand image and sustaining customer interest. This study aims to examine, describe, and analyze the influence of customer value and cafe atmosphere on brand image mediated by customer satisfaction. This research employs a quantitative approach, with a sample of 130 café restaurant customers in Malang City selected as respondents. Data were collected using questionnaires and analyzed using the Structural Equation Model (SEM) with Partial Least Squares (PLS). The results indicate that both customer value and café atmosphere have a positive and significant effect on customer satisfaction in café restaurants in Malang City. Furthermore, customer value, café atmosphere, and customer satisfaction each have a positive and significant effect on brand image. The findings also reveal that customer satisfaction mediates the influence of customer value and café atmosphere on brand image. This suggests that improving customer value and creating a favorable café atmosphere, supported by high customer satisfaction, will strengthen the brand image of café restaurants in Malang City and increase customer interest in visiting.